Pengaruh Perbedaan Konsentrasi Propilenglikol terhadap Karakteristik Fisik Hair Tonic Ekstrak Daun Katuk (Sauropus androgynus (L). Merr) - Daradasih, Elline; Devi, Sisca (Universitas Hamzanwadi, 2023)
Katuk leaf extract contains flavonoids which can stimulate hair growth by relaxing the muscles in the blood vessels around the hair follicles. One dosage form that is suitable for hair growth application is hair tonic preparations. An important component in the formulation of hair tonic is a thickener which can maintain the stability of the preparation. Propylene glycol is a thickening agent that can determine the physical characteristics of hair tonic preparations which are related to the stability of the resulting preparations. The purpose of this study was to determine the effect of different concentrations of propylene glycol on the physical characteristics of hair tonic katuk leaf extract (Sauropus androgynus (L.) Merr). This type of experimental research uses a completely randomized design (CRD) one factorial. The independent variables in this study were the concentration of propylene glycol 5%, 15% and 25%. Testing the physical characteristics of hair tonic preparations included organoleptic, clarity, pH, viscosity, and specific gravity. Data analysis used the ANOVA test with a 95% level of confidence then continued with the Post hoc test. The results of the physical characteristic test showed that the difference in the concentration of propylene glycol in hair tonic katuk leaf extract had an effect on the physical characteristics of viscosity (p<0.05).